FINANCIAL ANALYSIS OF ETAWAH CROSSBRED GOAT FARMS IN PEMPATAN VILLAGE, RENDANG DISTRICT, KARANGASEM REGENCY, BALI - A. W., GINTING; DOLOKSARIBU, L.; KAYANA, I. G. N. (Majalah Ilmiah Peternakan; Vol 26 No 2 (2023): Vol. 26 No. 2 (2023)DO - 10.24843/MIP.2023.v26.i02.p10, 2024)
Goat farmers generally do not realize the impact of flock size (FS) on the income resulted from their goat farm enterprises. The purpose of this study is to observe the impacts of FS i.e., FS1-10; FS11-20; FS21-30 on income, break-even point (BEP), and profit rate of etawah crossbred (PE) goat farm enterprises in Pempatan Village. A survey method used in this study was stratified purposive sampling procedure that was adopted to ensure the se- lection referred to PE breeders. Data were obtained through observation the goat cages of each farmer and with structured and unstructured interview techniques applying from October to December 2021. Data of the total costs, total income, profit rate, and BEP were analysed using financial analysis. Results showed the largest FS provided the largest annual total income IDR 44,990,000 ± 1,976,000. In contrast, the smallest FS provided the smallest amount of the annual total income IDR 5,601,000 ± 1,976,000. The Values of BEP production and price were 18 goats and IDR 1,212,200 ± 43,490/goat, respectively. Both values were smaller than the number of goats selling 30 ± 1 goats and the goat selling price IDR 1,800,000/goat in Pempatan Village annually. In summary, the PE goat farming enterprise was above the BEP providing profit rate 63.1 ± 3.7 %/year.